Characterisation and quantification of mucosal cytokine that induces epithelial histocompatibility locus antigen-DR expression in inflammatory bowel disease. - Lowes, JR; Radwan, P; Priddle, J; Jewell, D (1992)
Epithelial histocompatibility locus antigen (HLA) class II expression was studied to evaluate its induction by mucosal mononuclear cells in inflammatory bowel disease and to characterise the responsible cytokine. Unstimulated cells of the HT-29 epithelial cell line did not produce class II molecules. After being stimulated with the mitogenic lectin phytohaemagglutinin mucosal mononuclear cells released a cytokine that induced epithelial HLA-DR expression. The cytokine had the physicochemical and immunological characteristics of interferon-gamma, and no additional cytokines were detected.